Correlation Protein and Amino Acid Content in Feed Ingredients with Zinc Binding Protein - Muktiani, Anis; Prastiwi, Wahyu Dyah (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2014)
Abstract. The aim of this study was to assess the correlation between protein content (N) and the amino acid of the feed material to the holding capacity of zinc and to find out the type of amino acids that contribute to bind Zn. Nineteen feedstuffs used in the experiment, namely soybean meal, catton seed meal, coconut meal, palm meal, distillers dried grains with solubles (DDGS), soy sauce waste, tofu waste, blood meal, feathers meal, fish meal, poultry meat meal (PMM) and meat bone meal (MBM), shrimp head meal, cassava leaf flour, sesbania leaf flour, glandiflora leaf flour, leucaenia leaf flour, gliricidia leaf flour, calliandra leaf flour, paraserianthes leaf flour were used. Nitrogen content of all feed ingridient was analyzed using Kejhdahl. The material was immersed in a solution of ZnO with a ratio N: Zn = 10: 1 for 24 hours then dried, subsequently the samples were analyzed to Zn bound in the protein feedstuffs (Zn-proteinate) and amino acid levels. Regression analysis was conducted to determine the correlation between the protein and amino acid content of feed ingredients with Zn-proteinate generated. Results of the study found that the average efficiency of incorporation of Zn-proteinate amounted to 47.87%. Feed ingredients that have the highest level of incorporation of soybean meal (73.71%). There is a positive correlation between crude protein content with the level of incorporation of Zn (Zn-proteinate). The results of non-linear regression analysis of the amino acid to the Zn-proteinate indicate that there were four amino acids that have a positive correlation with Zn-proteinate that aspartic acid, glutamic acid, arginine and tyrosine. The conclusion of this study is to increase the protein content of feed ingredients and amino acids aspartic acid, glutamic acid, arginine and tyrosine lead to increased levels of Zn-proteinate (Zn incorporation). Key words : Zn proteinatee, amino acid, corelation, feed ingredients. Abstrak. Penelitian ini bertujuan untuk menemukan korelasi antara protein (N) dan asam amino dari berbagai bahan pakan sumber protein dengan daya ikat (inkorporasi) ion Zn pada pembuatan mineral organik Zn-proteinate. Sembilan belas bahan pakan digunakan dalam percobaan, yaitu bungkil kedelai, bungkil biji kapok, bungkil kelapa, bungkil sawit, distillers dried grains with solubles (DDGS), ampas kecap, ampas tahu, tepung darah, tepung bulu, tepung ikan, tepung kepala udang, poultry meat meal (PMM), meat bone meal (MBM), tepung daun ketela pohon, tepung daun turi, tepung daun lamtoro, tepung daun gamal, tepung daun kaliandra dan tepung daun sengon. Bahan-bahan tersebut direndam dalam larutan ZnO dengan perbandingan N : Zn = 10 : 1 selama 24 jam lalu dikeringkan dan dianalisis kadar Zn-proteinate serta kadar asam aminonya. Uji regresi dilakukan untuk mengetahui korelasi antara kadar protein dan asam amino bahan pakan dengan kadar Zn-proteinate yang dihasilkan. Hasil penelitian mendapatkan bahwa rata-rata efisiensi inkorporasi Zn-proteinate adalah sebesar 47,87%. Bahan pakan yang mempunyai tingkat inkorporasi tertinggi yaitu bungkil kedelai (73,71%). Terdapat korelasi positif antara kandungan protein kasar dengan tingkat inkorporasi Zn (kadar Zn-proteinate). Hasil analisis regresi non linier asam amino terhadap kadar Zn-proteinate menunjukkan bahwa terdapat empat asam amino yang mempunyai korelasi positif dengan kadar Zn-proteinate yaitu asam aspartat, asam glutamat, arginin dan tirosin. Kesimpulan dari hasil penelitian ini adalah peningkatan kadar protein bahan pakan dan kadar asam amino asam aspartat, asam glutamat, arginin dan tirosin menyebabkan peningkatan kadar Zn-proteinate (inkorporasi Zn). Kata kunci : Zinc, protein, asam amino, korelasi, Zn proteinate.